Research on Large-scale Air-conditioning Loads Participating in Peak Shaving. Issue 1 (August 2021) - Ding, Yifan; Xi, Weimin; Ma, Yahui; Jiang, Haiyan
Abstract: As a type of the elastic load, the demand-side controllable air-conditioning load can respond to electricity demand based on incentives or electricity prices. By adopting a reasonable control strategy for the optimal combination of controllable air-conditioning load groups, the air-conditioning loads of large-scale buildings can be guided to execute various dispatch commands of the power grid in the best response to electricity consumption. This paper constructs an air-conditioning load model. On this basis, a day-ahead dispatch model of the power grid with the extensive participation of central air-conditioning loads is established. The case shows that the participation of large-scale air-conditioning load in demand response can effectively reduce the peak load and realize the economic operation of the system.